Convergent mutation trajectories convert functional self-tolerance in IGHV4-34 B cells to genetic tolerance encoded in the antibody - Christopher J. Jara; Sherin Zachariah; Katherine J. L. Jackson; Timothy J. Peters; Etienne Masle-Farquhar; Deborah L. Burnett; Eric Lam; Megan Faulks; Amanda Russell; Lisa Miosge; Stewart Smith; David C. Tscharke; et al. (Proceedings of the National Academy of Sciences, 2025)
Preventing autoantibody secretion by rendering self-reactive B cells functionally silent through clonal anergy has long posed the question of why fill the circulating B cell repertoire with cells that cannot secrete antibody? Here we address this question from the perspective of B cells that comprise 5 to 10% of the human circulating repertoire, expressing self-reactive surface immunoglobulins employing the IGHV4-34 heavy chain variable element. Using gene targeting to construct mice expressing a representative human IGHV4-34 antibody on the surface of many B cells, we show these cells are prevented from autoantibody secretion by B cell clonal anergy marked by downregulation of surface IgM, induction of tolerance-response mRNAs, and exclusion from the marginal zone and B1 cell subsets. This functionally tolerant state is overridden when the IGHV4-34 B cells cross-react with a virus, which stimulates the self-reactive B cells to hypermutate in germinal centers. Within 16 d of infection, 99% of daughter cells have acquired one of five heavy chain mutations that diminish binding to self but preserve virus binding, and 33% had combined 2 or 3 of these mutations to make their antibodies genetically self-tolerant and virus specific. These results demonstrate, from the perspective of a pathologically important human autoantibody class and the world’s most successful virus vaccine, how human antibody specificity is sculpted in the progeny of anergic B cells to yield antibodies that bind a virus but not self.